1996
DOI: 10.12693/aphyspola.89.3
|View full text |Cite
|
Sign up to set email alerts
|

HgSe Based Mixed Crystals Doped with Fe Resonant Donors

Abstract: The article reviews the physical properties of semimagnetic semiconductors of the type Hg1-x-yFexΑ Se1-xΒzVI 1 and Hg1-x-yFexMnySe. Optical, magnetooptical, transport and magnetotransport experiments showed that in Hg1-xFexSe substitutional iron forms a resonant donor state whose energy is superimposed on the conduction band continuum. Resulting anomalous properties of electron scattering rate, i.e. strong enhancement of electron mobility (or drop of Dingle temperature), which occur in Hg1-xFexSe at low temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…semiconductors in which one can find coexisting magnetic ions of the same chemical nature but different charge states, was discussed in [75]. The DMS with the above property are not at all unusual: the best studied examples are the zero-gap II-VI compounds (HgSe and HgS) with Fe ions for which the 2+/3+ donor level is degenerate with the conduction band (see [76], [77] and the references therein). The different charge states of magnetic ions were also observed in III-V DMS [78][79][80].…”
Section: Double Exchangementioning
confidence: 99%
“…semiconductors in which one can find coexisting magnetic ions of the same chemical nature but different charge states, was discussed in [75]. The DMS with the above property are not at all unusual: the best studied examples are the zero-gap II-VI compounds (HgSe and HgS) with Fe ions for which the 2+/3+ donor level is degenerate with the conduction band (see [76], [77] and the references therein). The different charge states of magnetic ions were also observed in III-V DMS [78][79][80].…”
Section: Double Exchangementioning
confidence: 99%
“…On the basis of classical and quantum transport measurements it has been suggested that iron in β-ΗgS could create a deep, localized donor state resonant with the conduction band [3,4]. In particular, noticeable effect of low temperature mobility enhancement (well known from the previous investigations of similar II-VI semiconducting system: HgSe doped with Fe -see, e.g., [5]) was found in Hg1-x Fex S samples with the lowest possible Fe concentration (slightly below 2%) [3]. One of the necessary conditions to observe such effect is pinning at the Fermi energy to the resonant donor level and coexistence of empty and occupied donor states.…”
mentioning
confidence: 99%